Plant virus transmission during seed development and implications to plant defense system - Escalante, Cesar; Sanz-Saez, Alvaro; Jacobson, Alana; Otulak-Kozieł, Katarzyna; Kozieł, Edmund; Balkcom, Kipling S.; Zhao, Chaoyang; Conner, Kassie (Frontiers in Plant Science, 2024)
Most plants produce large amounts of seeds to disperse their progeny in the environment. Plant viruses have evolved to avoid plant resistance mechanisms and use seeds for their dispersal. The presence of plant pathogenic viruses in seeds and suppression of plant host defenses is a major worldwide concern for producers and seed companies because undetected viruses in the seed can represent a significant threat to yield in many economically important crops. The vertical transmission of plant viruses occurs directly through the embryo or indirectly by getting in pollen grains or ovules. Infection of plant viruses during the early development of the seed embryo can result in morphological or genetic changes that cause poor seed quality and, more importantly, low yields due to the partial or ubiquitous presence of the virus at the earliest stages of seedling development. Understanding transmission of plant viruses and the ability to avoid plant defense mechanisms during seed embryo development will help identify primary inoculum sources, reduce virus spread, decrease severity of negative effects on plant health and productivity, and facilitate the future of plant disease management during seed development in many crops. In this article, we provide an overview of the current knowledge and understanding of plant virus transmission during seed embryo development, including the context of host-virus interaction.